Which emotions make you healthier? - Herter, Márcia Maurer (2021)
Herter, M. M., Borges, A., & Pinto, D. C. (2021). Which emotions make you healthier? : The effects of sadness, embarrassment, and construal level on healthy behaviors. Journal of Business Research, 130(June), 147-158. https://doi.org/10.1016/j.jbusres.2021.03.016